Dietary Habits, Beneficial Exercise and Chronic Diseases Latest Advances and Prospects - Mitrou, Panagiota (2022)
Several lines of evidence indicate that healthy diet and exercise can prevent cardiovascular diseases, stroke, diabetes, and some types of cancer such as colon cancer, and smoking-related cancers. Dietary patterns defined as the quantities, proportions, variety, or combination of different foods and drinks, and the frequency with which they are habitually consumed are also associated with an increased or decreased incidence of chronic diseases. Lately, an association has been found between eating habits, exercise, and psychological and/or mental disorders. This Special Issue of Nutrients, entitled "Dietary Habits, Beneficial Exercise, and Chronic Diseases: Latest Advances and Prospects", contains 20 manuscripts, either describing original research or reviewing the scientific literature, focused on the relationship between dietary habits (macronutrients, micronutrients, etc.) and/or exercise with metabolic, cardiovascular, neurological, mental, rheumatic, inflammatory, gastrointestinal, odontostomatological, and other chronic diseases.